1998
DOI: 10.1128/jb.180.7.1973-1977.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Aspergillus nidulans nmrA Gene Involved in Nitrogen Metabolite Repression

Abstract: The gene nmrA of Aspergillus nidulans has been isolated and found to be a homolog of the Neurospora crassa gene nmr-1, involved in nitrogen metabolite repression. Deletion of nmrA results in partial derepression of activities subject to nitrogen repression similar to phenotypes observed for certain mutations in the positively actingareA gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 43 publications
2
79
0
Order By: Relevance
“…Currently, transcriptome analysis is in progress of F. fujikuroi areA and areB mutants grown under various nitrogen conditions to determine common and different target genes on a genome-wide scale. Alternatively, it is intriguing to speculate that the role of AreB has diverged between A. nidulans and F. fujikuroi, as it is the case for NmrA and the bZIP transcription factor MeaB (Andrianopoulos et al, 1998;Mihlan et al, 2003;Wong et al, 2007;Schönig et al, 2008;Wagner et al, 2010). Indeed, cross-species complementation revealed that the role of AreB is only partially conserved in the two fungal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, transcriptome analysis is in progress of F. fujikuroi areA and areB mutants grown under various nitrogen conditions to determine common and different target genes on a genome-wide scale. Alternatively, it is intriguing to speculate that the role of AreB has diverged between A. nidulans and F. fujikuroi, as it is the case for NmrA and the bZIP transcription factor MeaB (Andrianopoulos et al, 1998;Mihlan et al, 2003;Wong et al, 2007;Schönig et al, 2008;Wagner et al, 2010). Indeed, cross-species complementation revealed that the role of AreB is only partially conserved in the two fungal species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that this process depends on the RNA-binding protein RrmA (Król et al, 2013). At the protein level, the function of AreA/Nit2 is negatively regulated by binding to the nitrogen metabolite repressor NmrA under nitrogen repressing conditions, and deletion of nmrA led to partial de-repression of nitrogen-regulated genes (Jarai and Marzluf, 1990;Andrianopoulos et al, 1998;Lamb et al, 2003;Kotaka et al, 2008). In F. fujikuroi, it has also been shown that AreA interacts with FfNmr, a homologue of A. nidulans NmrA.…”
Section: Introductionmentioning
confidence: 99%
“…Unigene 95 encoded an NmrAlike protein that was specifically expressed during biotrophic growth in planta (Figure 4). NmrA is a repressor of the AreA global regulator of nitrogen metabolism (Andrianopoulos et al, 1988), and an AreA orthologue, CLNR1, has been shown to be essential for pathogenicity and the biotrophy to necrotrophy switch in C. lindemuthianum (Pellier et al, 2003). A homologue of the N. crassa CPC2 cross-pathway control gene (Mü ller et al, 1995) was also present in the library (unigene 114).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of ammonium, the process of nitrogen assimilation from less preferred sources, such as nitrate, urea, peptides, and amino acids, are regulated by nitrogen metabolite repression (Tudzynski, 2014). In ascomycota, nitrogen metabolite repression is controlled by a GATA transcription factor (Caddick, 1992), which is under the regulation of a co-repressor NmrA (Fu et al, 1988;Andrianopoulos et al, 1998). Additionally, bZIP transcription factors have been also shown to be involved.…”
Section: Effect Of N or P Starvation On Cellular Proteome In Serendipmentioning
confidence: 99%